Specific inhibition of in vitro Candida-induced lymphocyte proliferation by polysaccharidic antigens present in the serum of patients with chronic mucocutaneous candidiasis. - Fischer, A (1978)
A specific inhibitory activity of in vitro proliferative responses of normal human lymphocytes to Candida metabolic antigen was found in the serum of 6 out of 23 children with chronic mucocutaneous candidiasis. In each of the six patients, the presence of an inhibitory activity was associated with Candida-specific cellular defects, characterized by a negative-skin test and a lack of in vitro lymphocyte proliferation. The presence of a circulating inhibitor was detected during relapses of the disease and disappeared under antifungal therapy. This inhibitory effect was not associated with any toxicity on tested lymphocytes. The factor was shown to be nondialysable, thermostable, nonprecipitable with ammonium sulfate and absorbable on anti-Candida antibodies or concanavalin A-coupled agarose columns. Altogether, these results suggest that the inhibitory factor is not an immunoglobulin, but rather a polysaccharidic antigen of Candida albicans. An inhibition of Candida-induced proliferative response of normal human lymphocytes was also obtained by addition of polysacharide antigens or purified mannans from C. albicans to cultures. Candida polysaccharidic antigens appeared, therefore, to be involved in specific depression of cellular functions observed in chronic candidiasis.